Strategic thinking: The construction and validation of an instrument - Rodrigues, R.; Ferreira, A. I.; Neves, J. (Polish Psychological Bulletin, 2021)
The lack of instruments that evaluate strategic thinking and the fact that it is positively related to high levels of professional performance has led us to the development and validation of a questionnaire that allows us to measure it in an organizational context. This was done through three studies. First an exploratory study, in which 272 Human Resources (HR) professionals participated, allowed us to develop its items and analyze its psychometric properties. From it three factors were extracted: (1) systemic thinking, (2) vision towards the future and, (3) identification of new opportunities. Also, the results indicated the existence of a latent overall model of strategic thinking. Secondly, a confirmatory study, where 352 Human Resources professionals participated, intended to validate the results of the previous study. The same three factors, and a latent factor were replicated revealing that the model presented had an excellent adjustment. Furthermore, a third study was carried out in order to study the perceived relationship between strategic thinking, satisfaction, trust and customers’ retention. This study counted with the participation of 273 professionals who held positions of middle and upper management, key employees regarding the use of ST in organizations. The results of the three studies allow us to conclude that the Strategic Thinking Questionnaire is a valid instrument to analyze strategic thinking.